Variability studies of quantitative characters in Maize (Zea mays L.) - B. Bharathiveeramani, M. Prakash and A.Seetharam (Electronic Journal of Plant Breeding, 2012)
One hundred and forty four maize inbreds were evaluated for 15 different quantitative characters. Analysis of variance andthe phentotypic range showed the availability of considerable variation for all the characters studied. The differencebetween PCV and GCV was very low for all the characters except Anthesis - Silking interval, cob yield/plant and grainyield/plant which showed that there was very little environmental effect on these characters. Anthesis-silking intervalrecorded high PCV, GCV, heritability and genetic advance as per cent of mean. Characters such as grain yield/plant, cobyield/plant and ear height showed comparatively moderate PCV and GCV values, moderate to high heritability withmoderate genetic gain. This shows the presence of considerable variation among the inbreds for these traits and thepossibilities of improvement in these characters through selection. Days to 50% tasseling, days to 50% silking and numberof leaves/plant showed low PCV, GCV and GA with very high heritability suggesting that there is very little scope forimproving these characters by selection.